RISK FACTOR SEXUAL RISK BEHAVIOUR OF ADOLESCENTS: A LITERATURE REVIEW - Ahmad Dahlan Syam; Sigit Mulyono; Poppy Fitriyani (Universitas Islam Negeri Alauddin Makassar, 2023)
Background: Adolescence is a transitional phase from childhood to adulthood. The number of adolescents in Indonesia with a population range of 15-24 years old is as much as 20% of the total population of Indonesia. The high rate of risky sexual behavior in adolescents has a significant impact with the increase in the incidence of HIV / AIDS among adolescents. Objectives: this study was conducted to identify risk factors for adolescent sexual behavior. Methods: This study is a literature review obtained from five databases including science direct, embase, springerlink, proquest, and google schoolar. This review follows guidelines based on PRISMA. Results: There were nine articles obtained from this study, then analyzed using JBI and Coreq tools. Conclusion: Based on these findings suggest that factors influencing adolescents engaging in risky sexual behaviors are lifestyle, peers, economics, parenthood, academic, social, and spiritual efficacy. The factors that influence adolescents to engage in sexual behavior in the field are knowledge factors.